Adapting Barry Buzan’s theory to the impact of PKK on Kurdistan regional government’s security - Haidar Yasin Mohammad; Salih Omar Issa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The Position of security among states is so critical that they call it the highest policy in international politics. After the Cold War, Barry Buzan believed that security issues could not be interpreted from the same perspective. Because security has previously been defined from a narrow perspective and only the military dimension has been paid attention to. Buzan and his colleagues therefore believed that post-Cold War changes and many other objective circumstances no longer made one-dimensional security useful for interpretation; On the contrary, security must be viewed in a multidimensional way. Therefore, they invented the concept of multidimensional security and insisted that military security alone does not mean security, but four other dimensions such as political, economic, social and environmental are important. The importance and purpose of this discussion is due to the security of the Kurdistan Region as an entity that is trying to achieve security for citizens. Therefore, according to the descriptive-analytical method, the main question of the research is the role of the PKK and its impact on the security of the Kurdistan Region? Considering the history of the Kurdistan Regional Government (KRG) to date, we can say that the PKK has had a negative impact on the security of the Kurdistan Region. This negativity is due to the fact that the PKK does not only affect the security of the region militarily, but also threatens various areas such as economic, political, social and environmental.